Genetic diversity of the ghost-faced bat Mormoops megalophylla Peters, 1864 (Chiroptera: Mormoopidae) in Ecuador; implications for its conservation - Camacho, M. Alejandra; Leiva-D, Veronica; López-Wilchis, Ricardo; Burneo, Santiago F. (THERYA, 2017)
Mormoops megalophylla is a cave-dwelling bat distributed from southern United States across Central America to northern Peru. Its conservation status at a global level is of Least Concern, according to the IUCN Red List of Threatened Species; in Ecuador, however, it is included under the Vulnerable category due to the threats faced by the only two viable populations known. Individuals from each locality (Carchi and Pichincha) were captured and marked. The D-loop of the mitochondrial control region was obtained from wing membrane tissue samples, in order to analyze the geographic distribution of nucleotide and haplotype diversity of the populations, as well as gene flow between them. The molecular variation within and between populations was evaluated through a molecular variance analysis. A high haplotype diversity and a low nucleotide diversity were observed. The gene-flow estimator revealed that Carchi and Pichincha make up a single population coming from a single lineage. The network of haplotypes indicated that those with the highest frequency are shared in both localities; the largest number of unique haplotypes, however, was observed in Pichincha. The high haplotype diversity and low nucleotide diversity values in Ecuador are due to the fact that the ghost-faced bat populations may have experienced a fast-growing period from a low effective population size, with sufficient time to accumulate haplotype diversity, but insufficient to increase nucleotide diversity. The low genetic variability between both localities indicates the existence of a panmictic population that may have been split by factors such as habitat transformation, leading to isolated colonies. The preservation of this vulnerable species will depend on conservation efforts and studies that seek to supplement the analysis of genetic variability with other molecular markers, a continued monitoring of migratory processes, and inventorying of intermediate sites and localities with historical records.